A comprehensive teacher strategy for successful online learning process - Rizqi Lestari; Budi Astuti; Caraka Putra Bhakti (Universitas Ahmad Dahlan, 2020)
Online learning is one of education methods that uses internet access and technological devices as a medium of communication between teachers and students. The teacher can use online learning during a pandemic that requires students and teachers to do physical distancing or during the industrial revolution 4.0 that implements technology in various fields of life. Online learning has several advantages and disadvantages, especially concerning the student conditions and learning effectiveness. This research was a literature review of the teacher’s strategy to achieve successful online learning. Teachers need to develop strategies for successful online learning. Teachers can use audio-visual show to attract students' interests, not give too many assignments, and provide contextual tasks that are relevant to students’ daily life. Guidance and counseling teachers can carry out preventive services in collaboration with school principals and teachers to collect data of students who do not have access to technology devices. The teacher also could conduct online group discussions to increase students’ interaction and reduce boredom learning. Furthermore, the teacher could implement curative services through online counseling services to overcome problems in online learning.